SAT0639-HPR The Most Frequent Inquiries of Patients on Subcutaneous anti -TNF Alpha Therapies. (15th July 2016) - Pavic Nikolic, M.; Hocevar, A.
Abstract : Background: Subcutaneous TNFα blockers enable patients with inflammatory arthritis to better control their disease and subsequently improve the quality of their daily functioning. At our Department of Rheumatology trained nurses provide education about proper subcutaneous (s.c.) administration techniques and telephone counseling about different issues asked by patients concerning their treatment. One of the key components of patient education and counseling is to explain when to postpone the biologic therapy in case of infection or planned surgical procedure. Objectives: The aim of our study was to look at the most frequent questions raised by patients about their treatment. In addition we looked at a potential association between particular patient problem and specific subcutaneous TNFα blocker. Methods: Data was collected between January 2013 and May 2014 and included demographic data, prescribed anti-TNF drug, and description of the patient reported query regarding their s.c. anti-TNF treatment. Patient queries were grouped into six topics: skin reactions, infections, vaccinations, drug interactions, planned surgical procedures and other (Table 1 ). Appropriate statistical methods were used to analyze data. Results: During the observation period 98 patients (23% males, mean (SD) age 56.1 (13.9) years) treated with subcutaneous TNFα blocker asked for help using a telephone call. Patients were treated with the following s.c. anti-TNF drugs: certolizumab (9%), etanercept (27%), adalimumab (41%), and golimumab (23%). The most common patient problems on subcutaneous TNFα inhibitors are presented in Table 1 . In 22% of cases patients seeked telephone advice for other different health problems (swollen joints, drug ineffectiveness, potential adverse effects).We did not find any significant difference concerning particular TNFα blocker and the pertinent patient problem. Conclusions: Telephone assistance is valuable for patients. Patients request more information about their treatment and continuous patient education could improve outcomes in the management of inflammatory rheumatic diseases. Disclosure of Interest: None declared